2018
DOI: 10.1093/jxb/ery246
|View full text |Cite
|
Sign up to set email alerts
|

PbbHLH4 regulates floral monoterpene biosynthesis in Phalaenopsis orchids

Abstract: A basic helix-loop-helix transcription factor PbbHLH4 induces the biosynthesis of monoterpenes for floral scent in Phalaenopsis orchids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 75 publications
0
56
1
Order By: Relevance
“…The functions of these regulators with PeMYB11 for anthocyanin accumulation and pigmentation patterning were further investigated by a transient overexpression approach in Phalaenopsis orchids. 2015; Chuang et al, 2018). Agrobacterium tumefaciens containing various regulatory genes were infiltrated into white petals of Phalaenopsis Sogo Yukidian 'V39 alone or with various bHLH transcription factors and/or MYB27-and MYBx-like repressors.…”
Section: Other Regulatory Factors Related To Harlequin Flower Formatimentioning
confidence: 99%
“…The functions of these regulators with PeMYB11 for anthocyanin accumulation and pigmentation patterning were further investigated by a transient overexpression approach in Phalaenopsis orchids. 2015; Chuang et al, 2018). Agrobacterium tumefaciens containing various regulatory genes were infiltrated into white petals of Phalaenopsis Sogo Yukidian 'V39 alone or with various bHLH transcription factors and/or MYB27-and MYBx-like repressors.…”
Section: Other Regulatory Factors Related To Harlequin Flower Formatimentioning
confidence: 99%
“…In orchids, PbGDPS , which encodes GPP synthase, may play a key role in regulating the biosynthesis of monoterpenes (geraniol and linalool) in P. bellina [ 14 ]. In addition, the transcript levels of two TPS genes ( PbTPS5 and PbTPS10 ) are consistent with the production of geraniol and linalool in P. bellina [ 15 ], although their functionality has not yet been verified. Although geraniol is an important floral volatile compound in D. officinale , a medicinal orchid [ 7 ], the GES gene responsible for geraniol biosynthesis in D. officinale has not yet been characterized.…”
Section: Introductionmentioning
confidence: 76%
“…From D. officinale genomic annotation data, three candidate GES sequences with best matches to known GES proteins [ 6 , 12 , 13 , 15 ] were retrieved by BLASTN, and named DoGES1, DoGES2, and DoGES3 ( Table S1 ). Multiple sequence alignment demonstrated that three DoGES proteins had highly conserved aspartate-rich motifs (DDxxD) and NSE/DTE motifs at the C -terminal, and an RRX 8 W domain at the N -terminal ( Figure 2 ), suggesting that DoGES1-3 were all TPSs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…De novo transcript sequence reconstruction from RNA-seq using the Trinity platform for 11 diverse P. equestris tissue performed by Niu et al (2016), and obtained transcriptomes from root, stem, seed and floral organs, and found 24, 21, 22 and 7 disease resistance (R) genes in the flower bud, root, stem and in the 7-day-seeds, respectively and did not observe the YABBY gene family (use in determining leaf polarity) in roots and seeds. Eight transcripts have been identified during the comparative transcriptome analysis between scented and scentless orchids, among them PbbHLH4 regulates floral monoterpene biosynthesis in Phalaenopsis orchid (Chuang et al 2018). Phalaenopsis flowering locus VE (PaFVE) gene has been characterized by Koh et al (2018) via spatial and temporal expression studies.…”
Section: Introductionmentioning
confidence: 99%